The multifunctional Drosophila melanogaster V-ATPase is encoded by a multigene family. - Dow, J.A.T. (Journal of Bioenergetics and Biomembranes, 1999)
In animals, V-ATPases are believed to play roles in the plasma membrane, as well as endomembrane. To understand these different functions, it is necessary to adopt a genetic approach in a physiologically tractable model organism. For this purpose, Drosophila melanogaster is ideal, because of the powerful genetics associated with the organism and because of the unusually informative epithelial phenotype provided by the Malpighian tubule. Recently, the first animal "knockouts" of a V-ATPase were described in Drosophila. The resulting phenotypes have general utility for our understanding of V-ATPase function and suggest a screen for novel subunits and associated proteins. Genome project resources have accelerated our knowledge of the V-ATPase gene family size and the new Drosophila genes vhaSFD, vha100-1, vha100-2, vha100-3, vha16-2, vha16-3, vha16-4, vhaPPA1, vhaPPA2, vhaM9.7.1, and vhaM9.7.2 are described. The Drosophila V-ATPase model is thus well-suited to both forward and reverse genetic analysis of this complex multifunctional enzyme.